A COMPARATIVE CLINICAL STUDY TO EVALUATE THE EFFECT OF CHARAKOKTA MUTRAVIRECHANIYA MAHAKASHAYA IN MUTRAKRICHRA OR LOWER URINARY TRACT INFECTION - Aryamol A D; Umesh C; Gopal Krishna G (International Journal of Ayurveda and Pharma Research, 2020)
Mutrakrichra the disease of Mutravaha Srotas is caused due to Sanga (obstruction). Mutrakrichra means difficulty in micturition. Mutrakrichra can be compared to lower urinary tract infection (LUTI) symptoms. LUTI is the most common infection known to mankind and a common condition seen in general practice. Urinary tract infection affects more than 150 million people every year worldwide. Objective: To evaluate the effect of Mutravirechaniya Mahakashaya in LUTI and to compare its efficacy with Tab. Norfloxacin. Methods: 45 patients of either gender with the symptoms of LUTI were randomized into three groups of 15 patients each. Group A- received Mutravirechaniya Mahakashaya 50ml. Group B- received Tab. Norfloxacin 400mg and Group C- Mutravirechaniya Mahakashaya and Tab. Norfloxacin in the above mentioned dose for ten days. Efficacy outcomes were assessed through subjective parameters and routine urine and microscopic examination. Observation and results: When compared all the groups showed better results in relieving the clinical symptoms of LUTI. Overall patients treated with Mutravirechaniya Mahakashaya and Tab. Norfloxacin showed better results, but there was no significant difference between the groups (P<0.351). Conclusion: Mutravirechaniya Mahakashaya was able to meet the efficacy outcomes measures in comparison to Tab. Norfloxacin. Clinical effects of Mutravirechaniya Mahakashaya were similar to Tab. Norfloxacin owing to its diuretic, analgesic and anti-inflammatory properties.